A Multi-Step Topological Optimization Approach for Spacer Shape Design in Double-Sided SiC MOSFET Power Modules Considering Thermo-Mechanical Effects - Yuhang Guo; Ke Chen; Wentao Jiang; Longnv Li; Gaojia Zhu (Energies)
Double-Side-Cooled (DSC) power modules, widely utilized in various industrial and transportation applications, are favored for their remarkable high cooling efficiency and minimal packaging parasitics. To extend the life cycle, the design and optimization of metal or alloy spacers have garnered significant research attention due to their role in mitigating thermal-expansion-mismatch-induced stresses. Among the optimization approaches, topology optimization (TO) methods have the merit of generating innovative spacer shapes, thereby maximizing the buffering effects. However, without certain design considerations and constraints predetermined, the overall processes can become computationally costly. This paper proposes an efficient strategy for finding the optimized spacer topology for a double-sided 1700 V/400 A DSC SiC MOSFET power module. First, comparative thermal-stress investigations are carried out to predetermine the spacer height prior to TOs. Subsequently, to identify the appropriate optimization target, different objectives are employed in the TOs of a 2D simplified model. Following this, TO with the selected target function is performed on 3D simplified models featuring diverse spacer combination architectures, with the preferable one chosen based on the outcomes. Eventually, leveraging the predetermined spacer height, objective function, and preliminary structure, a 3D TO spacer design utilizing a full-domain model is conducted to validate the effectiveness of the proposed methodologies. The final spacer design reduces the maximum von-Mises stress in the attachment by 19.42% (from 111.78 MPa with brick spacers of the same height to 90.07 MPa). The proposed multi-step TO method can therefore be used to improve the thermo-mechanical lifetime of DSC power modules.